GENETIC ANALYSIS OF ARALIA CORDATA THUNB BY RAPD - Qu, Fan; Zhou, Jue; ZHOU, Zhou; LI, Huiyu; BURROWS, Elizabeth (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
In the research, genetic analysis of Aralia cordata Thunb. (Araliaceae) was conducted using randomly amplified polymorphism DNA (RAPD). 161 loci were detected with 12 RAPD primers. Percentage of Polymorphic Band (PPB) varied from 34.78% to 63.35%. All the samples were respectively collected from the eight provinces richest in Aralia cordata Thunb resources in China, including Hunan, Yunnan, Zhejiang, Sichuan, Jiangxi, Anhui, Shanxi and Gansu. The results showed that Hunan Province enjoyed the highest level of genetic differentiation and Gansu was the lowest. The total genetic diversity (HT) of RAPD, intraspecific genetic diversity (HS) and genetic diversity (DST) of the various places was respectively 26.33%, 11.14%, and 49.36%. The differentiation among the species accounted for 98.76% of total genetic diversity (GST). Based on the cluster results of genetic distance, the 8 samples were classified into three groups. It is concluded that Hunan Province enjoyed the highest level of genetic differentiation of Aralia cordata Thunb and Gansu was the lowest, which provides a basis for the taxonomic identification and germplasm resource research of Aralia cordata Thunb in the future.